Nonempirical calculations of CO 2 adsorption on (100) ZnO surfaces - Оралбеков, Н.Б.; Усеинов, А.Б.; Акылбеков, А.Т.; Даулетбекова, А.К.; Здоровец, М.В.; Ыбыраев, Н.С.; Дукенов, А.Б. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
A deep understanding of the interaction of these impurities with the active surface of the sensor at the atomic level plays a significant role in the development of solid-state systems for detecting bio- and gas mixtures. In our work, a computer simulation of the adsorption of a carbon dioxide molecule on a ZnO surface with various configurations and location on the surface was carried out. It is shown that the tridentate configuration is most energetically favorable, which probably arises in non-equilibrium conditions. In addition, the binding energy of a molecule weakly depends on concentration, and the presence of intrinsic defects on the surface (such as an oxygen vacancy) leads to a weakening of the binding energy. The formation of new substances (such H2CO) on the surface is in good agreement with the data obtained from the experiment, but has not yet been confirmed.